Outcomes of Management of Pediatrics Both Forearm Bone Fractures by Using Titanium Elastic Nailing System (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Forearm fractures include 25% of all infantile complaints. Forearm fractures account for 30 to 50% of all paediatric fractures and boys were more prone to forearm fractures. Paediatric diaphyseal bone fractures can be treated conventionally through closed manual reduction and casting as the abilities of the paediatric bones to remodel.Titanium Elastic Nails (TENS) is extensively used in children because it is innocuous. The aim of the study to recognize the management of pediatric bone forearm fractures using TENS. Materials and methods: A prospective study was carried out in the Department of Orthopedics, Chattagram Maa-O-Shishu Hospital Medical College from January 2018 to June 2022. A total of 45 patients (n=45) were enrolled in this study. Verbal consent was taken before recruiting the study population. Ethical clearance was taken from the hospital. The information was kept confidential only to be used for the study purpose. Results: Around three-fourths of the study population (34,75.6%) were male and only eleven patients were female and forty-two patients (42,93.3%) had no complaints of strenuous activity. Fractures involved the middle third in the most of the patients (22,48.9%). Closed reduction and internal fixation with titanium elastic nail system were done in forty-four patients (44,97.8%) and the result was excellent in most of the patients (42,93.3%) and satisfactory in three patients (3,6.7%.) Conclusion: Closed reduction and internal fixation with TENS appears to be acceptable treatment preference for the fixation of paediatric bone fractures. It provides exceptional functional consequences in terms of the range of motion and grip strength without chief complications.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 19-23